90 minutes in heaven : a true story of death & life - Piper, Don, 1950-; Murphey, Cecil (Grand Rapids, Mich. : Revell, 2004)
As he is driving home from a minister's conference, Baptist minister Don Piper collides with a semi-truck that crosses into his lane. He is pronounced dead at the scene. For the next 90 minutes, Piper experiences heaven where he is greeted by those who had influenced him spiritually. He hears beautiful music and feels true peace.
The accident -- My time in heaven -- Heavenly music -- From heaven to earth -- Earth to hospital -- The recovery begins -- Decisions and challenges -- Pain and adjustments -- Endless adjustments -- More miracles -- Back to church -- Opening up -- The clasping hand -- The new normal -- Touching lives -- Finding purpose -- Longing for home -- The why questions.
Includes bibliographical references (p. 207).
Keywords: Piper, Don, -- 1950-; Heaven -- Christianity; Near-death experiences -- Religious aspects -- Christianity; Future life -- Christianity; Near Death Experiences -- Religious Aspects -- Christianity; Piper, Don, -- 1950-; Heaven -- Christianity; Near-death experiences -- Religious aspects -- Christianity